Conservation management of large carnivores in Africa - M.G.L. Mills (Koedoe: African Protected Area Conservation and Science, 1991)
The conservation management of large carnivores in Africa is reviewed. In large protected areas the complexity of the relations between predators and prey, and between competing predators, indicate that these relationships should not be disturbed, even though, superficially, there may seem to be sound reasons to do so. Management action, however, may have to be taken against carnivores that break out of reserves. The related questions of translocation and re-introduction are also complex. Guidelines for considering whether to and how to implement these strategies are presented. It is stressed that adequate follow-up observations should be made after translocating or re- introducing carnivores, so that more information on the success of these strategies can be obtained. Much of Africa comprises rural areas inhabited by pastoralists. It may be possible to manage some large carnivore species in these areas to the mutual benefit of man and beast, but for this type of program to be successful, a well planned public relations campaign is essential.